(untitled) (Historia, 2021)
At first glance, Joyce’s South Africa in the 20th Century seems to be a rather odd publication meant as a coffee table book for a limited clientele or perhaps a reference book for school libraries. This book certainly fulfils these roles admirably, but, on consideration, it offers a great deal more. South Africa in the 20th Century is divided into eleven chapters – one for each decade of the 20th Century and a final one on the year 2000, which consists of spectacular colour photographs of Millennium illuminated and firework displays. Each chapter begins with a list of the landmarks of the decade (according to the author). This is followed by a year-by-year discussion of the decade. For each year, the author lists events, innovations, births, deaths and soon, with brief descriptions of those he feels deserve the most attention. The book is copiously illustrated with appropriate photographs, many in colour.